2002
DOI: 10.1007/pl00012424
|View full text |Cite
|
Sign up to set email alerts
|

Lower apoptosis rate and higher CD69 expression in neutrophils from atopic individuals

Abstract: These data suggest a potential role for neutrophils in the allergic inflammatory reaction through differences in apoptosis rates and CD69 expression between atopic and non-atopic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Wedi and co-workers [43] reported that prolonged peripheral blood eosinophil survival is a feature of inhalant allergy and extrinsic and intrinsic atopic dermatitis as compared with nonatopic subjects. Similarly, a more recent study suggested that eosinophils from atopic individuals display significantly higher viability as compared with non-atopic individuals in the absence of and in the presence of GM-CSF [44]. Furthermore, in mild asthmatic patients demonstrating a late asthmatic response, allergen challenge prolongs the survival of peripheral blood eosinophils [45].…”
Section: Delayed Eosinophil Apoptosis In Asthmamentioning
confidence: 96%
“…Wedi and co-workers [43] reported that prolonged peripheral blood eosinophil survival is a feature of inhalant allergy and extrinsic and intrinsic atopic dermatitis as compared with nonatopic subjects. Similarly, a more recent study suggested that eosinophils from atopic individuals display significantly higher viability as compared with non-atopic individuals in the absence of and in the presence of GM-CSF [44]. Furthermore, in mild asthmatic patients demonstrating a late asthmatic response, allergen challenge prolongs the survival of peripheral blood eosinophils [45].…”
Section: Delayed Eosinophil Apoptosis In Asthmamentioning
confidence: 96%
“…It is noteworthy that some molecular regulators of neutrophil apoptosis, such as CD69, SAA, and SHP, are practically not detectable in healthy people, but their count increases dramatically in some diseases. At the same time, increased CD69 and SAA expression is associated with suppression of apoptosis [ 91 , 96 , 97 ], while SHP, on the contrary, with its activation [ 76 , 46 ] ( Table 1 ). Local tissue lesions associated with acute circulatory disorders or trauma is the cause of the development of sterile inflammation accompanied by DAMP release and neutrophilic infiltration.…”
Section: Apoptosis Disturbances In Pathologymentioning
confidence: 99%